(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2019)
In this proposed project, the patients will perform the registration, once the patient is registered into the application then the patients are allowed to enter there scanning attributes of kidney diseases and then the user kidney disease stage level is determined by making use of C5.0 and Naïve Bayes supervised machine learning algorithm, the system provides, the user will get suggestions from the doctor at various level of kidney stage and if the user belongs to kidney stage 5 then patient will get suggestions patient will get suggestions as well as appointment request.